The changing macroeconomic response to stock market volatility shocks - Roel Beetsma; Massimo Giuliodori (Center for Economic Studies and ifo Institute (CESifo), 2011)
There is substantial consensus in the literature that positive uncertainty shocks predict a slowdown of economic activity. However, using U.S. data since 1950 we show that the macroeconomic response pattern to stock market volatility shocks has changed substantially over time. The negative response of GDP growth to such shocks has become smaller over time. Further, while during earlier parts of our sample both a slowdown in consumption and investment growth contribute to a reduction of GDP growth, during later parts, only the investment reaction contributes to the GDP slowdown. A variance decomposition for consumption growth shows that the contribution of stock market volatility becomes negligible as we go from earlier to later parts of the sample, while the corresponding decomposition for investment growth reveals an increase in the role of stock market volatility.
Keywords: E20; E31; E40; 330; Dow Jones index; stock market volatility shocks; economic growth; consumption; investment; sample splits